Change of appetite in patients with functional digestive disorder. Association with psychological disorders: A cross‐sectional study. Issue 1 (28th December 2017) - Fysekidis, Marinos; Bouchoucha, Michel; Mary, Florence; Airinei, Gheorghe; Bon, Cyriaque; Benamouzig, Robert
Abstract: Background and Aims: Changes in appetite are a frequent complaint in patients with functional gastrointestinal disorders (FGIDs). The aims of this study are to evaluate whether the changes in appetite are associated with specific FGIDs and to explore associations of these changes with symptoms of anxiety or depression. Methods: This study included 1009 consecutive FGID patients (71% female), aged 48.9 years who all filled out a Rome III questionnaire for the evaluation of FGIDs, submitted to a psychological evaluation of symptoms of anxiety, and completed the Beck Depression Inventory questionnaire. The patients were classified according to their appetite change using a 7‐point grading scale and split into three groups: those with appetite loss, those with no change in appetite, and those with increased appetite. Results: Among the 1009, 496 patients (49%) reported a change in appetite, of which 332 (33%) patients reported a decrease in appetite and 164 (16%) patients reported an increase in appetite. Appetite was not affected in 51% of patients. Changes in appetite depended on gender, body mass index and psychometric evaluation scores. Increased appetite did not have specific FGIDs associations, while decreased appetite was associated with esophageal, gastroduodenal, bowel, and anorectal symptoms. The presence of depressive symptoms was also a predictor for the majority of FGIDs in decreased appetite, while anxiety trait was significant for globus and dysphagia. Conclusions: Decreased appetite was associated with FGIDs, especially in the presence of depressive symptoms. A reduced appetite would help to predict psychological disorders associated with FGIDs. Financial disclosure: None declared. Legal registration: This study was a registered study in the French National Drug Agency (ANSM, Agence Nationale de Securité du Medicamentet des produits de santé, Study Number 2016‐A01120‐51). Competing interests: Michel Bouchoucha, Marinos Fysekidis, Florence Mary, Gheorghe Airinei, Cyriaque Bon, and Robert Benamouzig have no competitive interests.